Diskursus Peran Bank Sampah Guna Mengentas Kemiskinan dan Rehabilitasi Lingkungan dalam Pandangan Hukum Lingkungan - Gema Permana Rahman; Muhamad Afifullah; Eriz Syawaldi; Irwan Triadi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Used goods are often considered garbage, but waste management is a serious problem in Indonesia, especially with increasing waste consumption and high poverty rates. Bank Sampah is emerging as a solution by managing used goods that have economic value, governed by environmental regulations. Although Bank Sampah is growing, there is no clear regulation on the legal entity used, especially in cooperation with third parties. Waste Bank with a sharia financial system has also emerged, but it is not yet clear in accordance with the applicable sharia banking regulations. The approach method used is normative juridical, analysing laws and regulations through literature study with the main study material in the form of regulations and secondary and tertiary materials. The results showed that the Waste Bank is a government solution with the 3R principle, involving the participation of the community, business entities, and local governments. Islamic Waste Banks such as iqtishadia in Pasong Village, Sumenep, are not only a place for collecting waste, but also conduct community assistance programmes. The Waste Bank helps alleviate poverty and the environmental law approach is key in achieving effective structuring and improving the environment.